Kriteria Guru Sekolah Minggu sebagai Gembala Anak Berdasarkan Yehezkiel 34:11-16 - Jessica Jessica; Yanto Paulus Hermanto; Tony Tedjo (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
Sunday School ministry plays a pivotal role in introducing Jesus Christ as a Saviour to the children. As a children's pastor, Sunday School's teacher must have specific criteria to make the ministry grow even better. This research method is qualitative, followed by the descriptive analysis along with literature review toward the text in Ezekiel 34:11-16